2020
DOI: 10.1017/s0022029919000992
|View full text |Cite
|
Sign up to set email alerts
|

ACAA2 and FASN polymorphisms affect the fatty acid profile of Chios sheep milk

Abstract: The objective of the research reported in this research communication was the identification and association of single nucleotide polymorphisms (SNP) in the ovine DGAT1, FASN, SCD1 and ACAA2 genes with milk fat percentage and fatty acid (FA) content. Three consecutive monthly milk samplings were obtained from a total of 429 purebred Chios ewes during mid-lactation. Genotypic data were jointly analyzed with 1184 fat content and 37 718 FA percentage records using mixed models. The 3′ untranslated region (UTR) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Lipids from milk and feeds were extracted and methylated as described by Symeou et al . (2019) and (2020), and Tsiafoulis et al (2014), respectively. Milk atherogenic ( AI ) and desaturation index ( DI ) were determined and fat-corrected milk yield at 6% of fat content was estimated.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Lipids from milk and feeds were extracted and methylated as described by Symeou et al . (2019) and (2020), and Tsiafoulis et al (2014), respectively. Milk atherogenic ( AI ) and desaturation index ( DI ) were determined and fat-corrected milk yield at 6% of fat content was estimated.…”
Section: Methodsmentioning
confidence: 88%
“…Measurements for total fat, protein, and solids non-fat were performed with the use of Lactostar 3510 (Funke Gerber, Berlin, Germany) according to Tzamaloukas et al (2015). Lipids from milk and feeds were extracted and methylated as described by Symeou et al (2019) and (2020), and Tsiafoulis et al (2014, respectively. Milk atherogenic (AI) and desaturation index (DI) were determined and fatcorrected milk yield at 6% of fat content was estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Two cheese batches per feeding treatment were produced, and three cheese samples per batch were analyzed for FA content. Lipid isolation from feed, milk, and halloumi samples was performed and FA methyl esters (FAME) were prepared as described previously (Tzamaloukas et al 2015;Symeou et al 2020). FA profiles were generated by analyzing the FAME samples on a gas chromatography-mass spectrometer (GCMS-QP2010 Shimadzu, Duisburg, Germany) equipped with an HT280T autosampler (HTA, Brescia, Italy).…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
“…For example, a study examining gene expression differences in metabolism and function between intramuscular and subcutaneous adipocytes in cattle found that SCD was highly expressed in adipocytes and closely associated with fat formation [53]. ACAA2 can play an important role in fatty acid metabolism by promoting the differentiation of sheep precursor adipocytes into adipocytes [38,67]. The inhibition of FADS2 in essential fatty acid de ciency induces hepatic lipid accumulation via impairment of very lowdensity lipoprotein secretion [68].…”
Section: Discussionmentioning
confidence: 99%